Organizações da sociedade civil de interesse público e as parcerias com os municípios do estado de Pernambuco: um olhar sobre a atuação das OSCIPs à luz do ideário de sua criação - Melo, Eduardo Machado de (2010)
Analysis of the partnerships made between Civil Society Organizations of public Interest and municipalities of the interior of the State of Pernambuco in face of legal permissiveness. State and noeliberality. The State seen as inefficient and uncapable of rendering the services due by itself. The State Reform as a motivation to stimulate the transference of activities carried out by the State to private entities which would 'tend to public interests' disconnected from the so-called strategic nucleus made up of essential functions for the definition and execution of public policies. Bureaucracy and managerialism. Master Plan For The Reform of the State’s Infrastructurre. The transference of activities deemed non-State-exclusive seen as an alternative for the improvement of the State’s capacity to tend to social demands. Social or non-exclusive services. Publicization or Privatization? Third sector. Non-governmenal organizations. Non-profit organizations. Titles and qualifications granted to third-sector organisms. Social Organizations – SO’s: the attempt to privatize state organisms. Management contracts as a mechanism for the obtention of results. Civil society organizations of public interest -- CSOPI’s – and the new attempt to pass activities carried out by the State on to the private sector, the so-called 'third sector'. Partnership terms as a way to transfer a service to be rendered to a private party without the due bidding process. Voluntarism as a means in itself to render the services aimed by the patnership terms. The many breaches and vulnerabilities of the 9.790/1999 law – the CSOPI’s Law, considered the legal Mark of the third sector. The 'partnerships' between municipalities of the State of Pernambuco and organisms qualified as CSOPI’s with intentions diverging from those 'proposed' by the Law.